2021
DOI: 10.4103/abr.abr_252_20
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Selenium-Enriched Yeast Supplementation on Serum Thyroid-Stimulating Hormone and Anti-Thyroid Peroxidase Antibody Levels in Subclinical Hypothyroidism

Abstract: Background: In the subclinical hypothyroidism, T4 or T3 levels are normal and thyroid-stimulating hormone (TSH) is slightly high. Selenium deficiency can lead to thyroid dysfunction. The present study aims to investigate the effect of selenium supplementation on the thyroid hormone and anti-thyroid peroxidase antibody (anti-TPO AB) levels. Materials and Methods: In this double-blinded, randomized, placebo-controlled clinical trial, 42 patients with subclinical hypothyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Only six (19%) studies were prospectively registered and reported their planned analyses. 46 , 48 , 50 , 68–70 Eight (26%) of the studies reported the details of the randomization process. 40 , 48 , 58 , 61 , 65 , 70 , 71 , 76 Other common issues included a lack of power analysis and a clear description of the statistical analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Only six (19%) studies were prospectively registered and reported their planned analyses. 46 , 48 , 50 , 68–70 Eight (26%) of the studies reported the details of the randomization process. 40 , 48 , 58 , 61 , 65 , 70 , 71 , 76 Other common issues included a lack of power analysis and a clear description of the statistical analysis.…”
Section: Resultsmentioning
confidence: 99%
“…No other study came to such relevant conclusions, although in a recent meta-analysis, Se-Su seems to have a protective role against postpartum depression ( 44 ). A placebo-controlled clinical trial for subclinical hypothyroidism was not able to demonstrate that Se-Su had any significant effect on serum TPOAb and TSH levels ( 45 ). Therefore, facing this lack of evidence, it is not surprising that in these AITD-related conditions, most clinicians either do not recommend Se or have no information.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent animal study found that when mice were placed on a low selenium diet (0.02 mg/kg), selenium levels in the thyroid gland were maintained, but reduced selenoprotein expression was observed in the liver and kidneys, targets of thyroid hormones [ 214 ]. While selenium supplementation was reported to induce no significant therapeutic effect on patients with subclinical hypothyroidism [ 215 ], co-treatment of selenium was found to enhance the efficacy of levothyroxine sodium (LT4) in treating chronic lymphocytic thyroiditis patients with hypothyroidism, yielding greater improvements to inflammatory factors, compared to treatment with LT4 alone [ 216 ]. Selenium supplementation was also found to increase the efficacy of antithyroid drugs in the treatment of Graves’ disease [ 217 ].…”
Section: Signals From Brain To Bodymentioning
confidence: 99%